2010
DOI: 10.1017/s0007114510004319
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of psychotropic-like properties of a probiotic formulation (Lactobacillus helveticusR0052 andBifidobacterium longumR0175) in rats and human subjects

Abstract: In a previous clinical study, a probiotic formulation (PF) consisting of Lactobacillus helveticus R0052 and Bifidobacterium longum R0175 (PF) decreased stress-induced gastrointestinal discomfort. Emerging evidence of a role for gut microbiota on central nervous system functions therefore suggests that oral intake of probiotics may have beneficial consequences on mood and psychological distress. The aim of the present study was to investigate the anxiolytic-like activity of PF in rats, and its possible effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
802
3
25

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,139 publications
(887 citation statements)
references
References 75 publications
29
802
3
25
Order By: Relevance
“…Future studies should examine the relationship between howler GI microbiome composition and health directly by measuring health factors that might be influenced by the microbiome such as glucocorticoid levels, parasite abundance and diversity and immunoglobulin A levels (Macpherson et al, 2008;Neish, 2009;Messaoudi et al, 2010). Black howler monkeys living in small, highly disturbed forest fragments are reported to exhibit higher fecal glucocorticoid levels than those inhabiting less-disturbed forest (Martinez-Mota et al, 2007), and studies of several howler species, including black howlers in Palenque, have reported higher GI parasite diversity and abundance in primates inhabiting degraded areas compared with those in relatively undisturbed habitats (Eckert et al, 2006;Stoner and Gonzalez Di Pierro, 2006;Trejo-Macias et al, 2007;Vitazkova and Wade, 2007;Trejo-Macias and Estrada, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should examine the relationship between howler GI microbiome composition and health directly by measuring health factors that might be influenced by the microbiome such as glucocorticoid levels, parasite abundance and diversity and immunoglobulin A levels (Macpherson et al, 2008;Neish, 2009;Messaoudi et al, 2010). Black howler monkeys living in small, highly disturbed forest fragments are reported to exhibit higher fecal glucocorticoid levels than those inhabiting less-disturbed forest (Martinez-Mota et al, 2007), and studies of several howler species, including black howlers in Palenque, have reported higher GI parasite diversity and abundance in primates inhabiting degraded areas compared with those in relatively undisturbed habitats (Eckert et al, 2006;Stoner and Gonzalez Di Pierro, 2006;Trejo-Macias et al, 2007;Vitazkova and Wade, 2007;Trejo-Macias and Estrada, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in GI microbiome diversity may reduce microbial functional groups, making the microbiome less efficient, less resistant to disturbance and more susceptible to pathogenic invasion (Rosenfeld, 2002;Costello et al, 2012). Hosts with low GI microbiome diversity also exhibit increased stress responses (higher glucocorticoid levels) and reduced immune function (fewer cells that secrete local, strain-specific immunoglobulin A) (Macpherson et al, 2008;Neish, 2009;Messaoudi et al, 2010;Hooper et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…60 Other events that lead to a change in the composition of gut microbiota such as infection or use of probiotics can also change the level of anxiety. 89,[103][104][105] Further, it is shown that the behavioral phenotype of anxietyprone strains of mice is also dependent on their existing microbiota. For example, BALB/c mice exhibit a highly anxious phenotype that does not show much exploratory locomotion in a new environment, while NIH Swiss mice show less anxiety and more exploratory motions in the same environment.…”
Section: Stress Response and Anxietymentioning
confidence: 99%
“…This might occur through a variety of local pathways, such as competitive exclusion of other bacteria, the production of antibacterial bacteriocins or alteration in the fermentation capacity of the microbiota. Studies also demonstrate probiotics might alter motility (72) , reduce intestinal permeability (73,74) , normalise inflammatory profile (IL-10:IL-12) (75) , reduce visceral hypersensivity (73,76) , attenuate anxiety behaviours (77)(78)(79) and modulate brain activity (80) in IBS. Most probiotic supplementation studies in IBS do not assess the luminal or mucosal microbiota composition in order to provide plausible evidence that colonisation of the microorganism(s) and modification of the microbiota are in part responsible for any clinical improvement.…”
Section: Probioticsmentioning
confidence: 99%